THE INFLUENCE OF BENSON RELAXATION TECHNIQUE ON PAIN REDUCTION IN PATIENTS AFTER CESAREAN SECTION SURGERY - Desreza, Nanda; Riza, Saiful; Zarita, Nofrida (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
A Caesarean Section (C-section) is a surgical procedure in which a fetus is delivered through an incision made in the abdominal and uterine walls, provided that the uterus is intact, and the fetus weighs more than 500 grams. Abdominal incisions can cause pain. One non-pharmacological therapy that can be employed to alleviate post-operative abdominal pain in C-section patients is Benson Relaxation Therapy. This study aims to investigate the impact of Benson Relaxation Therapy on Pain Reduction in Post-Operative C-Section Patients. This research is categorized as a quasi-experimental study using a one-group pretest-posttest design approach. Data collection took place from August 15th to 26th, 2022, involving a population of 15 post-C-section mothers. Data were collected using both primary and secondary sources and analyzed using the Wilcoxon test, as well as univariate and bivariate analysis techniques. The study results showed a significant difference in pain levels before and after the administration of Benson Relaxation Therapy, with a p-value of 0.000 (<0.05). It is hoped that this research will enhance postpartum mothers' awareness of pain-reduction therapies, prompting them to consult healthcare professionals (doctors and nurses) and participate in seminars or workshops organized by relevant institutions.